Development of Kit Formulations for (99m)TcN-MPO: A Cationic Radiotracer for Myocardial Perfusion Imaging - Zheng, Yumin (J Labelled Comp Radiopharm, 2014)
The objective of this study was to develop a kit formulation for (99m)TcN-MPO to support its clinical evaluations as a SPECT radiotracer. Radiolabeling studies were performed using three different formulations (two-vial formulation and single-vial formulations with/without SnCl(2)) to explore the factors influencing radiochemical purity (RCP) of (99m)TcN-MPO. We found that the most important factor affecting the RCP of (99m)TcN-MPO was the purity of PNP5. (99m)TcN-MPO was prepared >98% RCP (n = 20) using the two-vial formulation. For single-vial formulations with/without SnCl(2), β-cyclodextrin (β-CD) is particularly useful as a stabilizer for PNP5. The RCP of (99m)TcN-MPO was 95 – 98% using β-CD, but its RCP was only 90 – 93% with γ-CD. It seems that PNP5 fits better into the inner cavity of β-CD, which forms more stable inclusion complex than γ-CD in the single-vial formulations. The results from biodistribution and imaging studies in Sprague-Dawley (SD) rats clearly demonstrated biological equivalence of three different formulations. SPECT data suggested that high quality images could be obtained at 0 – 30 min post-injection without significant interference from the liver radioactivity. Considering the ease for (99m)Tc-labeling and high RCP of (99m)TcN-MPO, the non-SnCl(2) single-vial formulation is an attractive choice for future clinical studies.